STUDI TENTANG PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP KOTA SAMARINDA BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NOMOR 02 TAHUN 2011 TENTANG PENGELOLAAN SAMPAH - Adrianus Nagong (Jurnal Administrative Reform, 2021)
This article will describe and analyze waste management by the Samarinda City Environmental Service based on Samarinda City Regional Regulation Number 02 of 2011 concerning Waste Management. This article uses qualitative research methods and data obtained by interview, observation, and documentation, and analyzed using an interactive analysis model. The research findings show that it has not been running optimally because there are still people who do not understand waste management starting from the source of waste, there are still people who litter, lack facilities and infrastructure, lack field workers, lack of awareness of community participation on cleanliness and weak supervision and sanctions people who break the rules. Keywords: management, waste, local regulations